Potential Benefits of Multimedia-Based Home Catheter Management Education in Patients With Peripherally Inserted Central Catheters: Systematic Review - Malale, Kija; Fu, Jili; Nelson, William; Gemuhay, Helena Marco; Gan, Xiuni; Mei, Zhechuan (JMIR Publications, 2020)
BackgroundIn recent years, there have been many suggestions to use multimedia as a strategy to fully meet the educational needs of patients with peripherally inserted central catheters. However, the potential benefits remain unreliable in the literature. ObjectiveIn this study, we identified the potential benefits of multimedia-based home catheter management education in patients with peripherally inserted central catheters and discussed the clinical implications. MethodsWe performed systematic searches of the PubMed, Cochrane Library, Embase Ovid, Medline, BioMed Central-cancer (BMC-cancer), ScienceDirect, and Google Scholar databases without date constraints until November 30, 2019. The methodological quality of the eligible studies was appraised using the Cochrane risk of bias tool. Narrative synthesis of the study findings was conducted. ResultsA total of 6 intervention studies met the inclusion criteria, including 3 randomized controlled trials and 3 case-control studies/quasi-experimental studies. The studies included a total of 355 subjects, including a total of 175 in the multimedia groups and 180 in the control groups. We identified 4 potential benefits to patients: (1) improved knowledge, (2) increased satisfaction, (3) reduced incidence of catheter-related complications, and (4) reduced number of cases of delayed care after complications. ConclusionsThe current systematic review highlights the potential benefits of multimedia-based home catheter management education for patients with peripherally inserted central catheters.